2016
DOI: 10.1111/nph.14219
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between soil and leaf mineral composition are element‐specific, environment‐dependent and geographically structured in the emerging model Arabidopsis halleri

Abstract: Summary Leaf mineral composition, the leaf ionome, reflects the complex interaction between a plant and its environment including local soil composition, an influential factor that can limit species distribution and plant productivity. Here we addressed within‐species variation in plant–soil interactions and edaphic adaptation using Arabidopsis halleri, a well‐suited model species as a facultative metallophyte and metal hyperaccumulator.We conducted multi‐element analysis of 1972 paired leaf and soil samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
219
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(251 citation statements)
references
References 59 publications
(90 reference statements)
27
219
2
3
Order By: Relevance
“…Differences in Cd concentrations in shoots between the results presented in this study and those obtained by Stein et al (2017) may be caused by the time of sampling (October for Stein et al [2017] and August for the data presented here) or the weather conditions in the year of sampling.…”
Section: Parameterscontrasting
confidence: 63%
See 4 more Smart Citations
“…Differences in Cd concentrations in shoots between the results presented in this study and those obtained by Stein et al (2017) may be caused by the time of sampling (October for Stein et al [2017] and August for the data presented here) or the weather conditions in the year of sampling.…”
Section: Parameterscontrasting
confidence: 63%
“…On the other hand, in this study, all of the individual plants from the M populations accumulated Cd in the shoots above 100 mg kg 21 dry weight. By contrast, Stein et al (2017) showed that a large number Presented data are means 6 SE (n = 8, except for C, where n = 6). Means followed by the same letter in a row are not significantly different from each other using the LSD test (P # 0.05).…”
Section: Influence Of the Environment On The Physiological Parametersmentioning
confidence: 85%
See 3 more Smart Citations